THE IMPACT OF CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE AND CAPITAL STRUCTURE ON FIRM VALUE: A STUDY ON ENERGY SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE DURING THE 2021-2023 PERIOD - Ni Made Crista Cahya Kireina; Anak Agung Gde Putu Widanaputra (Adisam Publisher, 2025)
Firm value is the perception of investors regarding the level of success of a company, as reflected through its stock price. This study aims to examine the impact of corporate social responsibility (CSR) disclosure and capital structure on the firm value of energy sector companies listed on the Indonesia Stock Exchange during the 2021-2023 period. This research adopts a quantitative approach with an associative research design. The sample consists of 16 companies selected through purposive sampling, totaling 48 observations over three years. The analysis technique used is multiple linear regression with the assistance of SPSS software. The results indicate that CSR disclosure has a positive and significant effect on firm value, while capital structure has no effect.